2017
DOI: 10.1016/j.eurpsy.2017.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and the relationship of somatic comorbidities to mortality in schizophrenia. A nationwide matched-cohort study

Abstract: A significant mortality gap - mainly associated with somatic comorbidities - was detected between patients with schizophrenia and individually matched controls. Improved medical training to address the disparity in mortality, and many other factors including lack of resources, access to and model of medical care, lifestyle, medication side effects, smoking, stigma, need for early intervention and adequate health care organization could help to better address the physical health needs of patients with schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 10 publications
1
57
0
6
Order By: Relevance
“…Earlier studies have reported an excess mortality of somatic diseases in patients with schizophrenia . Our results indicate that the largest difference in mortality rates between patients with schizophrenia and the general population is observed before the development of somatic multimorbidity.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Earlier studies have reported an excess mortality of somatic diseases in patients with schizophrenia . Our results indicate that the largest difference in mortality rates between patients with schizophrenia and the general population is observed before the development of somatic multimorbidity.…”
Section: Discussionsupporting
confidence: 50%
“…The main causes of death are somatic diseases, such as cardiovascular, respiratory, and cancer diseases . These causes of death are similar to the main causes of death observed in the general population, although the developments within somatic treatments have resulted in an improved survival following these and other somatic diseases , but data do not support similar improved survival following somatic diseases in patients diagnosed with schizophrenia .…”
Section: Introductionmentioning
confidence: 98%
“…Clozapine is recommended for use after two other antipsychotics have been ineffective and, therefore, is generally initiated later in the illness course than other antipsychotics. Since mortality may be particularly high in the early phase of the illness, the later use of clozapine could introduce a survival bias. Therefore, we conducted sensitivity analyses by excluding the first ten years of follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Bitter et al (11) highlighted the reduction in life expectancy among patients with schizophrenia. Of note is the fact that, compared with the controls, 20-year-old males with schizophrenia had their life expectancy reduced by 11.5 years and females by 13.7 years; the analogous numbers for 45-yearold schizophrenics were 8.1 and 9.6 years, respectively.…”
Section: Mortality In Schizophrenia and Pharmacological Treatmentmentioning
confidence: 99%